2013
DOI: 10.1523/jneurosci.3147-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Functional Specialization of Left Inferior Frontal Gyrus in Phonological and Semantic Fluency: The Crucial Role of Task Demands and Individual Ability

Abstract: Despite a large body of research, extant findings on the functional role of left inferior frontal gyrus (LIFG) in phonological and semantic fluency are still controversial. Based on cross-study comparisons, a recent meta-analysis of neuroimaging results suggests that posteriordorsal (Brodmann area, BA, 44) and anterior-ventral parts (BA 45) of LIFG contribute differentially to processes of phonologically and semantically cued word retrieval, respectively. In contrast, a subsequent functional magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 51 publications
10
111
1
1
Order By: Relevance
“…Brain [18F]FDG-PET imaging identified a significant hypometabolism in the left middle and inferior frontal gyri, in agreement with previous studies showing that this area is critically involved in the causation of dynamic aphasia [7]. In particular, functional imaging studies have demonstrated that phonological fluency, which was precociously and prominently impaired in our patient, is underpinned by the activation of the posterior left inferior frontal gyrus (Brodmann area 44) close to adjacent premotor areas [8]. …”
Section: Discussionsupporting
confidence: 90%
“…Brain [18F]FDG-PET imaging identified a significant hypometabolism in the left middle and inferior frontal gyri, in agreement with previous studies showing that this area is critically involved in the causation of dynamic aphasia [7]. In particular, functional imaging studies have demonstrated that phonological fluency, which was precociously and prominently impaired in our patient, is underpinned by the activation of the posterior left inferior frontal gyrus (Brodmann area 44) close to adjacent premotor areas [8]. …”
Section: Discussionsupporting
confidence: 90%
“…By contrast, the search strategy in phonologic fluency requires utilizing unusual and thus slower, more controlled associations based on the first letter of the words (Mummery et al, 1996). Variations in task demands between the two types of fluency have also been demonstrated to account for differences in the brain areas involved in the two tasks, most notably at the level of inferior frontal gyri (Katzev et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, phonologic fluency requires inhibiting the default semantic associations to search words according to the unusual 'first letter' association between them. Phonologic fluency has thus been advanced to load more strongly on the executive component than semantic fluency (Perret, 1974;Thompson-Schill et al, 1997;Thompson-Schill et al, 1998;Katzev et al, 2013), although control processes are also likely necessary in semantic fluency to shift between subcategories of items and resist the interferences from competing alternatives when a given semantic network is activated (Mummery et al, 1996;Reverberi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide additional evidence for impaired cerebral metabolism or respectively blood flow in the left IFG in MCI. We believe that such an effect is plausible because of this region's involvement in semantic and phonological processing (Costafreda et al, 2006;Katzev et al, 2013), in processes of empathy and working memory (Liakakis et al, 2011), and in tasks of self-awareness (Morin and Michaud, 2007).…”
Section: Reduced Epib In MCI Compared With Hcsmentioning
confidence: 98%